Complications of transradial versus transfemoral access for neuroendovascular procedures: a meta-analysis. (3rd September 2021) - Schartz, Derrek; Akkipeddi, Sajal Medha K; Ellens, Nathaniel; Rahmani, Redi; Kohli, Gurkirat Singh; Bruckel, Jeffrey; Caplan, Justin M; Mattingly, Thomas K; Bhalla, Tarun; Bender, Matthew T
Abstract : Background: Transradial access (TRA) has gained increased usage among neurointerventionalists. However, the overall safety profile of access site complications (ASCs) and non-access site complications (NASCs) of TRA versus transfemoral access (TFA) for neuroendovascular procedures remains unclear. Methods: A systematic literature review and meta-analysis using a random effects model was conducted to investigate the pooled odds ratios (OR) of ASCs and NASCs. Randomized, case–control, and cohort studies comparing access-related complications were analyzed. An assessment of study heterogeneity and publication bias was also completed. Results: Seventeen comparative studies met the inclusion criteria for final analysis. Overall, there was a composite ASC rate of 1.8% (49/2767) versus 3.2% (168/5222) for TRA and TFA, respectively (P<0.001). TRA was associated with a lower odds of ASC compared with TFA (OR 0.42; 95% CI 0.25 to 0.68, P<0.001, I 2 =31%). There was significantly lower odds of complications within the intervention and diagnostic subgroups. For NASC, TRA had a lower composite incidence of complications than TFA at 1.2% (31/2586) versus 4.2% (207/4909), P<0.001). However, on meta-analysis, we found no significant difference overall between TRA and TFA for NASCs (OR 0.79; 95% CI 0.51 to 1.22, P=0.28, I 2 =0%), which was also the case on subgroup analysis. Conclusion: On meta-analysis, the current literature indicates that TRA is associated with a lower incidence of ASCs compared with TFA, but is not associated with a lower rate of NASCs.